2008
DOI: 10.1186/cc6997
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in intensive care unit patients: a comparison between the RIFLE and the Acute Kidney Injury Network classifications

Abstract: Introduction Whether discernible advantages in terms of sensitivity and specificity exist with Acute Kidney Injury Network (AKIN) criteria versus Risk, Injury, Failure, Loss of Kidney Function, End-stage Kidney Disease (RIFLE) criteria is currently unknown. We evaluated the incidence of acute kidney injury and compared the ability of the maximum RIFLE and of the maximum AKIN within intensive care unit hospitalization in predicting inhospital mortality of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
3
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 26 publications
7
169
3
12
Order By: Relevance
“…The conclusion revealed that some participants with AKI were undiagnosed and no proportional increase between mortality rate and AKI stages. 19,20 Following the insufficiency of serum creatinine responsible for AKI, the next major quantum of deficiency in the field arose from the understanding that the limitations of the urine output criteria and inappropriately identifying prognostic factors of mortality in patients with AKI. 21,22 Because the factors including volume status and nutrition status that affect creatinine, serum creatinine was found to be subnormal standard biomarker for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion revealed that some participants with AKI were undiagnosed and no proportional increase between mortality rate and AKI stages. 19,20 Following the insufficiency of serum creatinine responsible for AKI, the next major quantum of deficiency in the field arose from the understanding that the limitations of the urine output criteria and inappropriately identifying prognostic factors of mortality in patients with AKI. 21,22 Because the factors including volume status and nutrition status that affect creatinine, serum creatinine was found to be subnormal standard biomarker for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies [47,48] that have compared the AKIN and RIFLE criteria have revealed no substantial differences. Chang et al [49] retrospectively investigated 291 critically ill patients and compared performance of the RIFLE and AKIN criteria for diagnosing and classifying AKI and for predicting hospital mortality.…”
Section: Criteria In General Icumentioning
confidence: 99%
“…Nevertheless, even after ageadjustment of the back-estimation formulae, the results did not improve. Unfortunately, many investigations have used an estimation of bSCr in up to 50% of their patients (11)(12)(13)(14)(15)29,30). As we and others have found (6,11,24), the estimated bSCr is inadequate when precise case adjudication is required, for example, in defining mild AKI stages (25).…”
Section: Discussionmentioning
confidence: 98%
“…Because the current models used to estimate bSCr values explain only a very limited amount of variation for any given age group, they have little validity for estimating bSCr as a replacement for the measured values. Therefore, the use of these formulae to classify a state of disease in clinical investigations (11)(12)(13)(14)(15)29,30) induces an important bias, and results should be interpreted very carefully.…”
Section: Discussionmentioning
confidence: 99%